REQUEST IN ENGLISH AS A SPEECH ACT - Zebokhon Musaeva Muzaffarovna (Galaxy International Interdisciplinary Research Journal, 2022)
Article aims to study importance of pragmatics and speech acts in learning English language. In oral communication challenge for English language learners is the speech act of requesting/asking. In terms of the way of expression, the request can be expressed directly or indirectly, and the degree of indirection can also vary significantly.